PENGARUH BENDING PADA ANTENA MIKROSTRIP PATCH BINTANG 24 DAN PATCH BINTANG 12 TERHADAP PARAMETER ANTENA DENGAN ORIENTASI BENDING ARAH SUMBU X - Muhammad Rizky Guntur Pratama; Muhammad Fauzan Edy Purnomo; Dwi Fadila Kurniawan (Jurnal Mahasiswa TEUB, 2023)
Microstrip antennas are used in various dimensions and shapes of microstrip antennas according to needs. In this use it allows bending of the microstrip antenna which changes the characteristics or parameters. In this research a microstrip antenna is designed with 24 star and 12 star patches and a staircase-shaped ground plane working at a frequency of 2.4 GHz. Design and simulation were carried out on the CST Studio Suite 2018 software and measurements were carried out with the ARINTS VNA. The simulation results show that bending causes yield degradation in the microstrip antenna parameters which include Return Loss, VSWR, Gain, Directivity, and Efficiency. the measurement results show that there is degradation in the Return Loss, VSWR, and Gain parameters. the smaller the bending radius that is done so that the antenna bends more, the performance quality value of the antenna parameters decreases.Keywords: Microstrip, Bending, Return Loss, VSWR, Gain, Bandwidth, Directivity, Efficiency, Axial Ratio, Polarization